Transcriptome-wide identification and expression profiling of the ERF gene family suggest roles as transcriptional activators and repressors of fruit ripening in durian - Gholamreza Khaksar (PLoS ONE, 2021)
The involvement of the phytohormone ethylene as the main trigger of climacteric fruit ripening is well documented. However, our knowledge regarding the role of ethylene response factor (ERF) transcription factor in the transcriptional regulation of ethylene biosynthesis during fruit ripening remains limited. Here, comprehensive transcriptome analysis and expression profiling revealed 63 ERFs in durian pulps, termed DzERF1–DzERF63, of which 34 exhibited ripening-associated expression patterns at three stages (unripe, midripe, and ripe) during fruit ripening. Hierarchical clustering analysis classified 34 ripening-associated DzERFs into three distinct clades, among which, clade I consisted of downregulated DzERFs and clade III included those upregulated during ripening. Phylogenetic analysis predicted the functions of some DzERFs based on orthologs of previously characterized ERFs. Among downregulated DzERFs, DzERF6 functional prediction revealed its role as a negative regulator of ripening via ethylene biosynthetic gene repression, whereas among upregulated genes, DzERF9 was predicted to positively regulate ethylene biosynthesis. Correlation network analysis of 34 ripening-associated DzERFs with potential target genes revealed a strong negative correlation between DzERF6 and ethylene biosynthetic genes and a strong positive correlation between DzERF9 and ethylene biosynthesis. DzERF6 and DzERF9 showed differential expression patterns in association with different ripening treatments (natural, ethylene-induced, and 1-methylcyclopropene-delayed ripening). DzERF6 was downregulated, whereas DzERF9 was upregulated, during ripening and after ethylene treatment. The auxin-repressed and auxin-induced expression of DzERF6 and DzERF9, respectively, confirmed its dose-dependent responsiveness to exogenous auxin. We suggest ethylene- and auxin-mediated roles of DzERF6 and DzERF9 during fruit ripening, possibly through transcriptional regulation of ethylene biosynthetic genes.